Epidemiological Study on Acute Diarrheal Outbreak Reported in Albaida Municipality After Danial Storm - Arij Mousa; Rmadhan Osman; Taha Gossbi (African Journal of Advanced Pure and Applied Sciences, 2024)
Background: The health impacts of floods lead to an increase in mortality and morbidity rates, primarily due to diseases such as diarrhea. Aim: To analyze the incidence of diarrheal diseases in “Albaida City” after the occurrence of Danial Storm. Method: A descriptive observational design to investigate the epidemiological disease burden and determinants of diarrheal disease in Albayda city, Libya, focusing on cases reported following the Danial Storm. The study conducted a comparative analysis of diarrheal cases and associated mortality recorded over four consecutive months post-flood, from September 2023 to December 2023. Results and discussions: The study reported a significant temporal association between the Danial Storm and the subsequent outbreak of diarrheal disease in the city. The increase in cases in the fourth-week period post-storm was clear. Many reasons describe the increase in diarrhea cases after the Danial Storm, such as the disruption and poor sanitation infrastructure. This caused contamination of water sources in the area. The secondary transmission wave, peaking in November despite the storm’s immediate effects subsiding, underscores the importance of sustained public health interventions. The data recorded two deaths of children under five. This highlights the critical need for increased awareness regarding the risks of using contaminated groundwater. While the outbreak was eventually controlled, likely due to interventions, such as clean water provision and awareness campaigns, the persistence of contaminated wells emphasizes the ongoing vulnerability of the region. The high percentage of contaminated wells (53%) indicates a pressing need for continued comprehensive solutions to ensure safe water access for the affected population. Conclusion: The study contributed valuable insights to the field of public health, informing future disaster response strategies and highlighting the urgent need for sustainable solutions in Libya to protect vulnerable populations from waterborne diseases.